The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2024
DOI: 10.1021/acs.nanolett.3c04300
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Plasmon-Assisted Resonant THz Detection in Single-Layer Graphene Transistors

José M. Caridad,
Óscar Castelló,
Sofía M. López Baptista
et al.

Abstract: Frequency-selective or even frequency-tunable terahertz (THz) photodevices are critical components for many technological applications that require nanoscale manipulation, control, and confinement of light. Within this context, gate-tunable phototransistors based on plasmonic resonances are often regarded as the most promising devices for the frequency-selective detection of THz radiation. The exploitation of constructive interference of plasma waves in such detectors promises not only frequency selectivity bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…The broadband operation of our photodetector is confirmed by noting that the value of the extracted relaxation time, τ , of our graphene photodetector with an average mobility of 70.000 cm 2 /(V⋅s) at a carrier density of n ≈ 10 15 m −2 is approximately 0.3 ps. At 0.3 THz, this corresponds to a device quality factor below unity, Q = 0.57 ( Q = 2π fτ , with f being the incoming THz frequency), typical of a THz photodetector working in the broadband regime [ 13 , 23 , 37 ], in a clear contrast with photodetectors operating at higher frequencies and exhibiting resonant detection ( Q ≫ 1) at THz fields [ 29 , 32 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The broadband operation of our photodetector is confirmed by noting that the value of the extracted relaxation time, τ , of our graphene photodetector with an average mobility of 70.000 cm 2 /(V⋅s) at a carrier density of n ≈ 10 15 m −2 is approximately 0.3 ps. At 0.3 THz, this corresponds to a device quality factor below unity, Q = 0.57 ( Q = 2π fτ , with f being the incoming THz frequency), typical of a THz photodetector working in the broadband regime [ 13 , 23 , 37 ], in a clear contrast with photodetectors operating at higher frequencies and exhibiting resonant detection ( Q ≫ 1) at THz fields [ 29 , 32 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…In practice, such high-quality samples are achieved by encapsulating the monolayer between hexagonal boron nitride (hBN) [ 26 , 27 ]. The device FET architecture is similar to the one used in several studies in literature reporting plasmonic photodetection [ 25 , 28 32 ], having a local top-gate (TG) electrode (which does not cover the entire device channel, see experimental details below). Moreover, the presence of a global back-gate (BG) electrode in the system allows us to independently dope channel regions not affected by the top-gate, tune the access resistance of these areas and therefore study their impact on the measured THz photoresponse.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the fabricated FET device could also act as a resonant THz photodetector due the plasmon resonance in the graphene channel, providing a potential plasmonic application in strong magnetic field. In the latest research, Caridad et al [89] have successfully fabricated single-layer graphene FETs and observed the plasmonic resonant THz detection for the first time. The fabricated short-channel FET detectors could achieve larger than 1 quality factor (Q ≫ 1), even under room temperature.…”
Section: Field Effect Transistormentioning
confidence: 99%